LIFE SKILL TRAINING MANAGEMENT IN AN EFFORT TO EMPOWER STUDENTS AT ISLAMIC BOARDING SCHOOLS - Tri Murdrika; Siti Nur'ain Pabiaiye; Vebriyanti Isilaku (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
This research is motivated by the importance of life skill training management in an effort to empower students in Islamic boarding schools to be able to live independently and contribute to society. The purpose of this study is to find out how life skill training management is carried out at Al-Falah Gorontalo Islamic Boarding School, including the planning, implementation, and evaluation stages. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation, as well as data analysis of the Miles and Huberman models. The results of the study show that training planning has not been well documented, even though the implementation of activities is quite effective, especially in sewing and tataboga training supported by professional instructors. However, the evaluation stage is not optimal because there is no systematic assessment instrument. The impact of this research emphasizes the importance of strengthening life skills training management so that pesantren can produce students who are qualified, independent, and ready to face global challenges